2004
DOI: 10.1128/jvi.78.18.9740-9749.2004
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Interleukin-7 Induces Proliferation of Naive Macaque CD4+and CD8+T Cells In Vivo

Abstract: Interleukin-7 (IL-7) regulates T-cell homeostasis, and its availability is augmented in lymphopenic hosts. Naive CD8؉ T cells transferred to lymphopenic mice acquire a memory-like phenotype, raising the possibility that IL-7 is the biological mediator of this effect. Here, we provide direct evidence that IL-7 induces the acquisition of memory-cell markers not only in CD8؉ T cells but also in CD4 ؉ T-cell subsets in immunecompetent Indian rhesus macaques. The increase of these memory-like populations was depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 32 publications
4
66
1
1
Order By: Relevance
“…Studies of IL-7 administration to uninfected and SIV-infected macaques have demonstrated a proliferative effect on CD4 ϩ and CD8 ϩ T cells expressing both memory and naïve phenotypes (27,28,38). Analogous results were obtained more recently in human cancer patients (39), as well as in HIV-1-infected individuals (M. Lederman, personal communication).…”
Section: Discussionsupporting
confidence: 60%
“…Studies of IL-7 administration to uninfected and SIV-infected macaques have demonstrated a proliferative effect on CD4 ϩ and CD8 ϩ T cells expressing both memory and naïve phenotypes (27,28,38). Analogous results were obtained more recently in human cancer patients (39), as well as in HIV-1-infected individuals (M. Lederman, personal communication).…”
Section: Discussionsupporting
confidence: 60%
“…IL-7 maintains survival and homeostatic proliferation of naive and memory T cells in vivo (5)(6)(7)(8)(9)(10). In vitro, however, it has been reported that naive T cells do not proliferate in response to IL-7 (63-65), whereas memory T cells have been reported to slowly cycle (Ref.…”
Section: Discussionmentioning
confidence: 99%
“…We interpret the above results to reveal the operation of a homeostatic mechanism that leads to increased cycling in the N T cell pool as the pool shrinks, perhaps as a consequence of increased availability of cytokines that regulate survival and cycling of N T cells (24). For example, IL-7 is believed to be the main regulator of N T cell turnover, and its administration to monkeys has been shown to increase N T cell proliferation (28). Based on our recent findings (19,29,30), the reduction in naïve T cell representation and diversity resulting from a mechanism of this kind would have the potential to adversely affect the induction of protective immunity.…”
Section: Discussionmentioning
confidence: 99%